IMPACT OF PHYSICAL THERAPY ON PELVIC FLOOR DYSFUNCTION AND SEXUAL HEALTH IN POSTPARTUM WOMEN (Journal of Medical & Health Sciences Review, 2025)
This study aims to investigate the impact of physical therapy on pelvic floor dysfunction and its subsequent effects on sexual function, incontinence, pelvic floor distress, and quality of life in postpartum women. A total of 100 postpartum women with diagnosed pelvic floor dysfunction participated in the study. Descriptive statistics were used to summarize participant characteristics, including age, parity, time postpartum, and baseline measures of pelvic floor dysfunction. Pre- and post-therapy assessments were conducted using standardized measures, including the Incontinence Impact Questionnaire (IIQ7), Pelvic Floor Distress Inventory (PFDI20), Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ12), and the Short Form 36 (SF36) for quality of life. Pelvic floor strength was assessed through physical examination. The results revealed significant improvements in sexual function (p = 0.023), with a moderate to strong positive correlation between sexual function and quality of life (r = 0.72, p = 0.001). Incontinence impact and pelvic floor distress showed trends of improvement but did not reach statistical significance. Pelvic floor strength showed no significant change post-therapy (p = 0.782). The study also observed a significant negative relationship between pelvic floor distress and sexual function (r = -0.32, p = 0.012). These findings suggest that while physical therapy can significantly improve sexual function and overall quality of life, its impact on incontinence and pelvic floor strength may require further attention. The study highlights the importance of addressing sexual health in pelvic floor dysfunction management, suggesting potential areas for refining physical therapy protocols for postpartum women.